Clinically used selective oestrogen receptor modulators increase LDL receptor activity in primary human lymphocytes. (8th January 2015) - Cerrato, F; Fernández‐Suárez, M E; Alonso, R; Alonso, M; Vázquez, C; Pastor, O; Mata, P; Lasunción, M A; Gómez‐Coronado, D
<x xml:space="preserve">Abstract</x> Background and Purpose Treatment with selective oestrogen receptor modulators (SERMs) reduces low‐density lipoprotein (LDL) cholesterol levels. We assessed the effect of tamoxifen, raloxifene and toremifene and their combinations with lovastatin on LDL receptor activity in lymphocytes from normolipidaemic and familial hypercholesterolaemic (FH) subjects, and human HepG2 hepatocytes and MOLT‐4 lymphoblasts. Experimental Approach Lymphocytes were isolated from peripheral blood, treated with different compounds, and 1, 1′‐dioctadecyl‐3, 3, 3, 3′‐tetramethylindocarbocyanine perchlorate (DiI)‐labelled LDL uptake was analysed by flow cytometry. Key Results Tamoxifen, toremifene and raloxifene, in this order, stimulated DiI‐LDL uptake by lymphocytes by inhibiting LDL‐derived cholesterol trafficking and subsequent down‐regulation of LDL receptor expression. Differently to what occurred in HepG2 and MOLT‐4 cells, only tamoxifen consistently displayed a potentiating effect with lovastatin in primary lymphocytes. The SERM‐mediated increase in LDL receptor activity was not altered by the anti‐oestrogen ICI 182 780 nor was it reproduced by 17β‐oestradiol. However, the tamoxifen‐active metabolite endoxifen was equally effective as tamoxifen. The SERMs produced similar effects on LDL receptor activity in heterozygous FH lymphocytes as in normal lymphocytes, although none of them had a potentiating effect with lovastatin in heterozygous FH lymphocytes. The SERMs had no effect in homozygous FH lymphocytes. Conclusions and Implications Clinically used SERMs up‐regulate LDL receptors in primary human lymphocytes. There is a mild enhancement between SERMs and lovastatin of lymphocyte LDLR activity, the potentiation being greater in HepG2 and MOLT‐4 cells. The effect of SERMs is independent of oestrogen receptors but is preserved in the tamoxifen‐active metabolite endoxifen. This mechanism may contribute to the cholesterol‐lowering action of SERMs.